Home Office – Problems and Challenges of Business Management - Mironova, Nadia; Boyadzhiev, Atanas (Research Papers, 2025)
Work organisation, coordination of processes and control are key effectiveness factors, that are tested in remote work. Along with the undisputable advantages of remote work, problem arise that can return this practice in its start position of unpopular and denied. The paper contains an author’s model of the factors for optimizing the management of remote work, based on a study of 4 scientific articles.